(untitled) (American Journal of Interdisciplinary Research and Development, 2024)
Legal persuasion techniques are a fundamental aspect of the practice of law, as lawyers seek to influence judges and juries through the strategic use of rhetorical strategies. This article explores the various methods and approaches employed by legal professionals to effectively persuade decision-makers in courtrooms. By examining the role of rhetoric in legal advocacy, this study aims to shed light on the nuanced techniques used to present compelling arguments, shape perceptions, and ultimately secure favorable outcomes for clients.